DEVELOPING WATER WHEEL-INTEGRATED STUDENT WORKSHEETS: A STRATEGY FOR ENHANCING ENVIRONMENTAL CARE ATTITUDES - Unayah, Habibatul; Rasyid, Muhammad; Rizky, Ihza; Suyanta, Suyanta; Yanuarief, Cecilia; Sulistiyawati, Sulistiyawati (Universitas Labuhanbatu, 2025)
Purpose- This study aims to design and test student worksheets (LKPD) using simple water wheel media, and to cultivate an environmental care attitude among junior high school students.Methodology- This research is a Research and Development (R&D) with the 4-D model (define, design, develop, disseminate). This research was carried out at SMP IT Ibnu Abbas with 34 students of eighth grade as participants. The data collection is done using the pre-test, post-test, and environmental care attitude questionnaire.Findings-Validation analysis reveals a predominant average score of 94% (very valid category) towards the suitability of worksheets for instilling the attitude of environmental care and its advantage in the science subject as determined from teacher and student questionnaires. The outcomes showed that there was an effect of simple water wheel media on students' attitude to care for environment and conceptual understanding, average gained N-gain = 0.86 (in the high category).Significance- This study shows how innovative, hands-on media have the potential to support science education and promote students’ sense of responsibility for environmental sustainability.Keywords: Environmental Care Attitudes, Student Worksheet, Water wheel